2016
DOI: 10.1002/cssc.201501560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium on the Mechanisms of Biomass Pyrolysis Studied using Complementary Analytical Techniques

Abstract: Complementary analytical methods have been usedto study the effect of potassium on the primary pyrolysis mechanisms of cellulose and miscanthus. Thermogravimetry, calorimetry, high temperature 1 H NMR (in-situ and real time analysis of the fluid phase formed during pyrolysis) and water extraction of quenched char followed by SEC/MS-ELSD (size exclusion chromatography coupled with mass spectrometry and evaporative light scattering detector have been combined). Pyrolysis was conducted under fixed bed conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 70 publications
(222 reference statements)
4
33
0
Order By: Relevance
“…Potassium was shown to prevent the production of acids, anhydrosugars, acetol, and xylose, while K 3 PO 4 promotes hemicellulose char, gas, and H 2 O (Bulushev and Ross, 2011;Le Brech et al, 2016;Zhang et al, 2017), which is in line with the present study. Furthermore, K 3 PO 4 mostly inhibited the primary hemicellulose oxygenates but mostly catalyzed lignin, as confirmed by the considerable increase in phenolic derivatives (Lu et al, 2013;Le Brech et al, 2016;Zhang et al, 2017).…”
Section: Catalytic Effects On Bio-oil Energy Density and Selectivitysupporting
confidence: 92%
See 1 more Smart Citation
“…Potassium was shown to prevent the production of acids, anhydrosugars, acetol, and xylose, while K 3 PO 4 promotes hemicellulose char, gas, and H 2 O (Bulushev and Ross, 2011;Le Brech et al, 2016;Zhang et al, 2017), which is in line with the present study. Furthermore, K 3 PO 4 mostly inhibited the primary hemicellulose oxygenates but mostly catalyzed lignin, as confirmed by the considerable increase in phenolic derivatives (Lu et al, 2013;Le Brech et al, 2016;Zhang et al, 2017).…”
Section: Catalytic Effects On Bio-oil Energy Density and Selectivitysupporting
confidence: 92%
“…Clinoptilolite has been reported to catalyze the decomposition of lignin, yielding a bio-oil rich in phenolic compounds, and the amount of alkylphenols, pyrocatechols, and BTEXs (benzene, toluene, ethylbenzene and xylenes) generated from lignin decomposition also increased by clinoptilolite (Lee et al, 2016). Potassium was shown to prevent the production of acids, anhydrosugars, acetol, and xylose, while K 3 PO 4 promotes hemicellulose char, gas, and H 2 O (Bulushev and Ross, 2011;Le Brech et al, 2016;Zhang et al, 2017), which is in line with the present study. Furthermore, K 3 PO 4 mostly inhibited the primary hemicellulose oxygenates but mostly catalyzed lignin, as confirmed by the considerable increase in phenolic derivatives (Lu et al, 2013;Le Brech et al, 2016;Zhang et al, 2017).…”
Section: Catalytic Effects On Bio-oil Energy Density and Selectivitymentioning
confidence: 99%
“…with heating rates of 10, 20 and 30 °C min -1 , respectively. These results are in a line with the work reported by Brech et al 50 and a distinguishing lignin pyrolysis peak at around 700 °C was described by Yang et al 48 . Alvarez et al studied the combustion of twenty-eight common biomass types, including miscanthus and they reported that miscanthus showed two temperature ranges of combustion of 240-340 and 450-550 °C using the DTG data 51 .…”
supporting
confidence: 93%
“…The increased stability of carbon can be explained by the catalytic effect of AMs on biomass pyrolysis, such as enhanced cross-linking reactions (e.g., dehydration forming C=C or C-O-C) resulting in a highly cross-linked biochar, compared to biochar from untreated biomass 34,35 .…”
Section: Resultsmentioning
confidence: 99%